2021
DOI: 10.37231/jmtp.2021.2.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework of Factors Affecting SME Development: Moderating Factor on the Relationship between Determinant Factors Selection and Performance of SMEs in Indonesia

Abstract: Just a little part of SMEs are fruitful in accomplishing remarkable execution and maintainable development, The writing shows that there is as yet a hole for powerful approaches to expand the size of that division. This paper expects to contribute in filling the hole by distinguishing factors influencing SME execution and, subsequently, their turn of events; and to build up a reasonable system clarifying their connections. The writing uncovers that despite the fact that there is positive connection between gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…They also need to deliver the products quickly. This study has confirmed the previous researches conducted by Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22], and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. DM also affects CA positively.…”
Section: ) Structural Model Testing (Inner Model)supporting
confidence: 92%
See 1 more Smart Citation
“…They also need to deliver the products quickly. This study has confirmed the previous researches conducted by Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22], and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. DM also affects CA positively.…”
Section: ) Structural Model Testing (Inner Model)supporting
confidence: 92%
“…DM has a positive effect on CA Valdez Palazuelos, O., and Sánchez Beltrán [18] , Gakiria [19] and Obeidat, U., Obeidat, B., Alrowwad, A., Alshurideh, M., Masadeh, R., and Abuhashesh [20] . DM has a positive effect on MP Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22] and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. Inn has a positive effect on CA Distanont, A., and Khongmalai [5], Olazo [24], Puspita, L. E., Christiananta, B., and Ellitan, [25], Udriyah, U., Tham, J., and Azam [26].…”
Section: Literature Reviewmentioning
confidence: 99%